2013
DOI: 10.1088/2043-6262/4/4/045004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of silver nanoparticles deposited on silica by γ -irradiation and preparation of PE/Ag nano compound masterbatches

Abstract: Silver nanoparticles (AgNPs) deposited on silica were synthesized by gamma Co-60 irradiation of Ag+ dispersion in silica/ethanol/water mixture (9/80/20:w/v/v). The reduction of Ag+ is occurred by hydrated electron (e−aq) and hydrogen atom (H•) generated during radiolysis of ethanol/water. The conversion doses (Ag+ →  Ag0) were determined by UV–Vis spectroscopy. The synthesized AgNPs/silica were characterized by transmission electron microscopy (TEM) and x-ray diffraction (XRD), which showed the size of AgNPs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…The content of AgNPs deposited on zeolite 4 A analyzed by ICP-AES was of about 1.2% (w w −1 ). Results of our previous study on doping AgNPs onto silica by gamma 60 Co irradiation method indicated that the size of AgNPs determined also by XRD was of about 23 nm, which was in fair correlation with particles size estimated from transmission electron microscopy (TEM) images [16]. Both doped products namely AgNPs/Z and AgNPs/SiO 2 have almost the same AgNPs content of around 1.0-1.2% (w w −1 ).…”
Section: Characteristics Of Agnps/zeolitementioning
confidence: 57%
“…The content of AgNPs deposited on zeolite 4 A analyzed by ICP-AES was of about 1.2% (w w −1 ). Results of our previous study on doping AgNPs onto silica by gamma 60 Co irradiation method indicated that the size of AgNPs determined also by XRD was of about 23 nm, which was in fair correlation with particles size estimated from transmission electron microscopy (TEM) images [16]. Both doped products namely AgNPs/Z and AgNPs/SiO 2 have almost the same AgNPs content of around 1.0-1.2% (w w −1 ).…”
Section: Characteristics Of Agnps/zeolitementioning
confidence: 57%
“…The amount of Ag needs to be controlled to get the optimal number of active sites and an even distribution of Ag is needed so that the Ag/SiO 2 composites have consistent performance. Many attempts have been devoted to realising it, including spray [48], deposition [49][50], sol-gel [51][52][53], impregnation [54], coating [55], and irradiation methods [56].…”
Section: Introductionmentioning
confidence: 99%
“…Gamma irradiation induces ionization and excitation of the water molecules, generating radiolytic molecular and radical species such as solvated electrons, hydroxyl radicals, and hydrogen atoms. The solvated electrons and hydrogen atoms reduce the metal ions to metal atoms, which coalesce to form more nanoparticles [ 52 ].…”
Section: Resultsmentioning
confidence: 99%